Analisis Efisiensi dan Efektifitas Laju Perpindahan Panas pada Alat Heat Exchanger tipe Double Pipe dengan Aliran Searah: Indonesia - A B Pratama; Al Qadry; J F HT Saragi; E P D Boangmanalu; F T H Sinaga; Kadriadi (Cered Indonesia Institute, 2023)
Double pipe heat exchangers have been widely used in various fields, one of which is in the industrial. The design of this heat exchanger has undergone many changes and modifications. This aims to get efficiency and effectiveness so that it can achieve maximum work on the tool. The focus of this research is to calculate and analyze the efficiency and effectiveness of the rate of heat transfer in a double pipe type heat exchanger with unidirectional flow. The data collection method was direct observation of the device, with an interval of two minutes for each test. The results of this study indicate that the effect of time variation on Vh = ±700 l/h, Vc = ±500 l/h fixed on the double pipe type, it can be concluded, at 2 minutes with Vh = ±700 l/h, efficiency is obtained 1.46% and effectiveness = 0.476. The longer the time in data retrieval, the efficiency increases. This can be seen in the table of research results, at 8 minutes Vh = ±700 l/h, efficiency = 1.478% and effectiveness = 0.919.